1997
DOI: 10.1139/cjpp-75-5-431
|View full text |Cite
|
Sign up to set email alerts
|

Active <SUP>22</SUP>Na<SUP>+</SUP> transport by the intact lung during early postnatal life

Abstract: The lung relies upon epithelial active transport of Na+ to aid in the clearance of fluid from its air spaces. Because it is unknown whether the rate of active Na+ transport by the distal lung epithelium varies during early postnatal age, we performed studies in young guinea pigs (7 and 30 days after birth). We used a single pass isolated perfused lung model in which a Krebs Ringer bicarbonate solution containing 22Na+, [14C]sucrose, and FITC-dextran was placed into the air spaces of the lungs, and apparent per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One of these Na ϩ channels is the amiloridesensitive epithelial Na ϩ channel (ENaC) that is composed of ␣-, ␤-, and ␥-subunits (6). However, it has been shown that normal mammalian lung epithelia have both an amiloridesensitive and an amiloride-insensitive component to their active Na ϩ transport both in vivo (24) and in vitro (8,25). Presently, the molecular basis of this amiloride-insensitive Na ϩ transport is poorly understood.…”
mentioning
confidence: 99%
“…One of these Na ϩ channels is the amiloridesensitive epithelial Na ϩ channel (ENaC) that is composed of ␣-, ␤-, and ␥-subunits (6). However, it has been shown that normal mammalian lung epithelia have both an amiloridesensitive and an amiloride-insensitive component to their active Na ϩ transport both in vivo (24) and in vitro (8,25). Presently, the molecular basis of this amiloride-insensitive Na ϩ transport is poorly understood.…”
mentioning
confidence: 99%
“…Dichlorobenzamil does not block epinephrine-induced fluid absorption in fetal lambs, but it attenuates fluid absorption in 6-wk-old lambs and totally blocks absorption in 6-mo-old lambs (40,41). The amount of amilorideinsensitive Na ϩ transport stabilizes after birth in the guinea pig as there are similar amounts of amiloride-insensitive apical to basolateral movement of 22 Na across the lung epithelia of 7-and 30-day-old animals (66).…”
Section: Amiloride-insensitive Na ϩ and Fluid Transport In The Fetalmentioning
confidence: 85%
“…Normal mammalian lung epithelia have been shown to have both an amiloride-sensitive and an amiloride-insensitive component to their active Na ϩ transport both in vivo (e.g., Ref. 28) and in vitro (10,17,29). In vivo, this amiloride-insensitive component may represent up to 50% of the total AFC (23).…”
mentioning
confidence: 98%